Utilizing BIM Technology in the Design Process of Hydrotechnical and Land Reclamation Facilities - Janusz Michał Filipczyk; Karol Krystian Plesiński; Kacper Cedro (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The paper presents the results and experiences related to the use of BIM technology in hydraulic and land reclamation projects. The authors rely on their extensive experience gained from various projects in the field. The article aims to demonstrate modern BIM technology’s potential and possibilities in designing hydraulic and land reclamation structures.